Effect of Reprocessing Palm Fiber Composite on the Mechanical Properties - Sivakumar, Dhar Malingam; Radzai, Said; Rivai, Ahmad; Ahadlin, Mohd Daud; Subramonian, Sivarao (Trans Tech Publications, Switzerland, 2014)
Concern for the environment, both in terms of limiting the use of finite resources and the need to manage waste disposal, has led to increasing pressure to recycle materials at the end of their useful life. This work describes the effects of reprocessing on the mechanical properties of oil palm fiber reinforced polypropylene composites (PFC). Composites, containing 30wt% fiber with 3wt% Maleate Polypropylene as a coupling agent, were reprocessed up to six times. For this composite, tensile strength (TS) and Young modulus (YM) were found to decrease by 9.6% and 4.7% after being reprocessed for six times. Flexural strength was found to decrease by 23.8% with increased number of reprocessing. The hardness numbers of the composite were found to increase by 7.43% from 72.10 to 77.89 after the sixth reprocessing. In general the degradation on the mechanical properties is considered to be small and PFC has potential to be reprocessed.